Taking Wittgenstein at his word : a textual study - Fogelin, Robert J. (Princeton monographs in philosophy., 2009)
Taking Wittgenstein at His Word is an experiment in reading organized around a central question: What kind of interpretation of Wittgenstein's later philosophy emerges if we adhere strictly to his claims that he is not in the business of presenting and defending philosophical theses and that his only aim is to expose persistent conceptual misunderstandings that lead to deep philosophical perplexities? Robert Fogelin draws out the therapeutic aspects of Wittgenstein's later work by closely examining his account of rule-following and how he applies the idea in the philosophy of mathematics. --From publisher's description.